A Four-Year Review of Occupational Injuries among Health Care Workers in a Tertiary Care Hospital - Zaidi, Moazzam; Behisi, Marwan (Ibnosina Journal of Medicine and Biomedical Sciences, 2025)
In the demanding health care sector, occupational injuries are prevalent and diverse, affecting health care workers' physical health and quality of life, and resulting in disability. There is a dearth of studies that comprehensively assessed diverse occupational injuries by using registered data over an extended period.Thus, this study aimed to investigate the burden of work-related injury in a tertiary care hospital.This study examined data collected from January 2017 to December 2020 at Johns Hopkins Aramco Healthcare, a tertiary care hospital in Dhahran, Saudi Arabia. A total of 187 health care workers with occupational injuries, registered in the Exposure Prevention Information Network (EPINet), were considered in the analysis.Blood and body fluids exposures (BBFEs) accounted for 56.7% (95% confidence interval [CI]: 52.34, 59.89) of all occupational injuries, while falls, slips, trips, and collisions made up 15% (95% CI: 12.47, 18.73). Needlestick injuries accounted for 48.1 and 84.9% of all occupational and BBFE injuries, respectively. The majority (38.7%) of BBFE happened at the operating theaters, followed by the emergency room (28.3%). Note that 60.4% of all injuries and 57.3% of BBFEs were experienced by nurses. The highest number of injuries was documented in 2019 and 2020.BBFEs and falls, slips, trips, and collisions were the most common occupational injuries, with nurses being the most affected. Nearly half of these incidents involve needlestick injuries, highlighting the need for strict safety protocols, regular training, use of personal protective equipment, patient handling protocols, and improved ergonomics.
Keywords: occupational injuries; health care workers; hospital; EPINet; Saudi Arabia